A One Health Perspective on Multidrug Resistance Amongst Iberian Exotic Pet Owners - Fábio Cardoso-Freitas; Stéphanie M. Mota; Vanessa Silva; Albert Martinez-Silvestre; Ângela Martins; Patrícia Poeta (Veterinary Sciences)
Understanding owners’ realities and perceptions may be crucial to helping veterinarians be more effective in their daily work. Noticing the lack of publications in this area, specifically on exotic pets, prompted us to gather insights into non-traditional companion animal owners. A survey was conducted, resulting in 541 respondents from Portugal and Spain. The results were characterised based on demographics, data on trade and antibiotic and parasiticide use, and the relations between these variables. We found that there is still a considerable part of unregistered animals and that, overall, owners acknowledged antimicrobial resistance and inadequate use of parasiticides. Hopefully, these data will help veterinarians in tackling these problems and enhance owners’ education and compliance.